Mucormycotic Osteomyelitis Involving the Maxilla: A Rare Case Report and Review of the Literature - Rajesh Arani; S. N. H. Afsar Shareef; H. M. Khuthija Khanam (Case Reports in Infectious Diseases)
Osteomyelitis is an inflammatory process of bone and marrow contents. These changes in bone are primarily seen in soft tissue followed by calcified tissue. It is an opportunistic infection due to the complication of some other conditions rendering the host susceptible to disease. Consequences of this infection range from draining tract to malignant transformation. Various etiological factors are involved in origin of the disease; among them, fungal origin is rare. Specific feature in fungal osteomyelitis is the involvement of maxillary sinus with a complaint of sinusitis associated with diabetes mellitus. Here, we discuss a case of osteomyelitis with fungal infection involving the maxilla. The patient is under medication for the past five years due to diabetes.